2011
DOI: 10.1128/jvi.05418-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Endogenous Retrovirus-Specific T Cell Responses in Vertically HIV-1-Infected Subjects

Abstract: Human endogenous retrovirus (HERV)-specific T cell responses in HIV-1-infected adults have been reported. Whether HERV-specific immunity exists in vertically HIV-1-infected children is unknown. We performed a cross-sectional analysis of HERV-specific T cell responses in 42 vertically HIV-1-infected children. HERV (-H, -K, and -L family)-specific T cell responses were identified in 26 of 42 subjects, with the greatest magnitude observed for the responses to HERV-L. These HERV-specific T cell responses were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
(26 reference statements)
2
26
0
Order By: Relevance
“…Early support for the induction of HERV antigen expression in HIV-1-infected subjects was provided by our observation that T cell responses to a variety of HERV-derived peptides are detectable in HIV-1-infected subjects but not in uninfected controls (25,26). Supporting the in vivo relevance of these responses, we observed that strong HERV-specific T cell responses were associated with control of HIV-1 replication (25,27).…”
Section: Figuresupporting
confidence: 60%
See 1 more Smart Citation
“…Early support for the induction of HERV antigen expression in HIV-1-infected subjects was provided by our observation that T cell responses to a variety of HERV-derived peptides are detectable in HIV-1-infected subjects but not in uninfected controls (25,26). Supporting the in vivo relevance of these responses, we observed that strong HERV-specific T cell responses were associated with control of HIV-1 replication (25,27).…”
Section: Figuresupporting
confidence: 60%
“…HERV-K(HML-2)-Env-and Gag-specific T cell responses detectable by 15-mer peptides are rare (29). Hence, to generate additional HERV-K(HML-2)-specific T cell clones we screened subjects using optimal HERV-K(HML-2) determinants identified in our previous studies (25)(26)(27). We generated a CD8 + T cell clone specific for the HERV-K(HML-2)-Pol epitope FAFTI-PAI from an individual with early (<1 year) HIV-1 infection and determined this response to be HLA-B*51 restricted.…”
Section: Cross-reactive Hiv-1/herv-k(hml-2)-specific T Cells Exist Anmentioning
confidence: 99%
“…The consequence of this increased expression of transmissible HK2 viruses, for both HIV-1-infected cells and the HIV-1-infected individual, remains to be elucidated. However, it is important to note that expression of HK2 epitopes, and perhaps transmissible HK2 viruses, on HIV-1-infected cells render these cells susceptible to lysis by immune T cells and antibody responses directed against HK2, creating a tool that conceivably could be used to eradicate HIV-1 infection (93)(94)(95).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have detected antibody responses to HERV-K in a majority of HIV-1-positive patients but not in uninfected donors (41,54). Similarly, T cell responses to HERV-K were observed in HIV-1-infected patients but not in healthy donors (19,49,51). Furthermore, upregulation of HERV-K RNA was detected (14-17, 19, 40) in plasma samples of HIV-1-infected individuals, in HIV-1-infected T cells (17,38), and in HIV-1 Tat-transfected T cells (23).…”
mentioning
confidence: 99%